DEVELOPMENT OF COGNITIVE ACTIVITY OF PRIMARY STUDENTS THROUGH DIDACTIC GAMES IN A DIGITAL EDUCATIONAL ENVIRONMENT (Universal International Scientific Journal, 2026)
This article highlights the pedagogical importance of didactic games used in a digital educational environment in developing the cognitive activity of primary school students. It also analyzes the possibilities of using interactive methods and digital technologies to activate students' cognitive activity. It is argued that didactic games are an important tool for increasing students' interest, developing independent thinking, and increasing educational efficiency.
Keywords: digital education, didactic games, cognitive activity, primary education, interactive methods, educational technologies.